PET radiotracers: crossing the blood–brain barrier and surviving metabolism - Pike, Victor W. (Trends in pharmacological sciences (Regular ed.), 2009)
Radiotracers for imaging protein targets in the living human brain with positron emission tomography (PET) are increasingly useful in clinical research and in drug development. Such radiotracers must fulfill many criteria, among which an ability to enter brain adequately and reversibly without contamination by troublesome radiometabolites is desirable for accurate measurement of the density of a target protein (e.g. neuroreceptor, transporter, enzyme or plaque). Candidate radiotracers can fail as a result of poor passive brain entry, rejection from brain by efflux transporters or undesirable metabolism. These issues are reviewed. Emerging PET radiotracers for measuring efflux transporter function and new strategies for ameliorating radiotracer metabolism are discussed. A growing understanding of the molecular features affecting the brain penetration, metabolism and efflux transporter sensitivity of prospective radiotracers should ultimately lead to their more rational and efficient design, and also to their greater efficacy.